Tax Avoidance dan Faktor yang Mempengaruhinya - Yolanda Pratami; Nisa Maharani (P3M Politeknik Negeri Bengkalis, 2025)
This research aims to test and analyze the influence of capital intensity, sales growth and institutional ownership variables on tax avoidance in coal mining companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The population in this study was 34 coal mining companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The research sample was selected using a purposive sampling technique to obtain 13 companies that met the criteria during the research time period. Data analysis uses multiple linear regression analysis techniques. Based on the results of tests that have been carried out, it shows that partially the capital intensity variable has a significant negative effect on tax avoidance, sales growth has a significant negative effect on tax avoidance and institutional ownership has a significant negative effect on tax avoidance. Simultaneously, the variables capital intensity, sales growth and institutional ownership have a significant effect on tax avoidance.